Establishing Knowledge Management As A Tool For Competitive Advantage: A Study In Malaysian Electronic Business - Chang, Clare Shiau Wei (2005)
The hyper competitiveness of the global economy has brought a consensus on the importance of organisational knowledge as a basis of competition. Knowledge management has become a hotly discussed topic among the academia as well as in the corporate world worldwide.